The prognostic importance of BCR-ABL transcripts in Chronic Myeloid Leukemia: A systematic review and meta-analysis. (February 2021) - Ghalesardi, Omid Kiani; Khosravi, Abbas; Azizi, Ebrahim; Ahmadi, Seyed Esmaeil; Hajifathali, Abbas; Bonakchi, Hossein; Shahidi, Minoo
Highlights: Meta-analysis performed of 54, 034 patients from 34 studies. Overall prevalence is much higher in the e14a2 compared to the e13a2 39 % and 54 %, respectively. Dual transcription of e13a2/e14a2 was 1.11 %. The ratio of male to female is higher in the e13a2 group compared to e14a2 (1.08 and 0.856, respectively). Criteria related to the response to the TKIs have been discussed. Abstract: Background: Chronic Myeloid Leukemia (CML) is characterized by the overproduction of BCR-ABL, a tyrosine kinase with constitutive activity, in which the majority of CML patients have e13a2 or e14a2 transcripts. Reckoned the possible associations between the hematologic and molecular features of the disease, a profound understanding of different aspects of this neoplasm would be provided. Method: The authors implemented a systematic literature search, utilizing the terms published articles or internationally accepted abstracts from PubMed, Embase, Medline, Cochrane library before January 2019. Weighted mean proportion and 95 % confidence intervals (CIs) of CML prevalence calculated using a fixed-effects and a random-effects model. Statistical heterogeneity was evaluated using the I2 statistic. Results: 34 studies for a total of 54, 034 Patients were selected and included in the review. Results revealed that compared to e13a2 group, the overall estimated prevalence is much higher in the e14a2 (39 % and 54 %, respectively). Besides, the overall estimated prevalence ratio of male to female was higher in the e13a2 group in comparison to e14a2 (1.08 and 0.856 respectively). The overall estimated prevalence of dual transcription of e13a2/e14a2 was 1.11 %, and male/female overall estimated prevalence ratio was 1.18. Conclusion: This meta-analysis of CML patients demonstrated the e14a2 as the more common transcript type. Usually, the e14a2 transcript is prevalent in females, whereas e13a2 and dual transcription of e13a2/e14a2 are more common in men. These data explicate that the differences in proportion are not by chance. This is crucial, as the transcript type is a variable suspected to be of prognostic importance for the treatment-related response, the outcome of treatment, and the rate of treatment-free remission.